Los delitos socioeconómicos en América Latina: especial referencia a Perú, Colombia, Argentina y Ecuador - Hernández Quintero, Hernando A. (2025)
With the rise of State interventionism in the economy, which can be seen at the beginning of the twentieth century, some Criminal Statutes sanction behaviors that injure or endanger such intervention, that is, economic crimes. This trend, which arose in Europe, spread to Latin America in the eighties and is evident in the Penal Codes issued from that moment on. This article seeks to analyze the way in which these criminal behaviors appear and are updated in the legislation of Latin America.